MAPPING CRITICAL THINKING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS IN THE CITY OF A THOUSAND RIVERS BASED ON LOCAL WISDOM - Irhasyuarna, Yudha; Yamin, Moh.; Fahmi, Fahmi; Yulianti, Yuyun Eka; Muslim, M.; Rahmati, Pramita Dwi; Maulidia, Maulidia; Sadiqin, Ikhwan Khairu; Rahman, M. Rezki; Ali, Akhmad Chaidir (Journal of Banua Science Education, 2023)
Learning will be successful if students do not memorize the information they obtain but can criticize the information they obtain, relate their condition and the surrounding environment to this information, and use it to make changes. This research was conducted to measure the level of critical thinking of junior high school students in the City of a Thousand Rivers on natural science subject matter based on local wisdom. The research results illustrate that students' critical thinking skills still tend to be low, this requires continuous improvement to train students' critical thinking skills to achieve one of the educational goals.Keywords:Â Critical Thinking Skills, Mapping, Middle School Students.Pembelajaran akan berhasil ketika siswa bukan menghafalkan informasi yang didapatkannya, tetapi mampu mengkritisi informasi yang diperolehnya, mampu menghubungkan kondisi diri dan sekitarnya dengan informasi tersebut, dan menggunakannya untuk melakukan suatu perubahan. Penelitian ini dilakukan untuk mengukur tingkat berpikir kritis peserta didik SMP di Seribu Bungai pada materi pelajaran ilmu pengetahuan alam berbasis kearifan lokal. Hasil penelitian menggambarkan bahwa keterampilan berpikir kritis peserta didik masih cenderung rendah, hal ini mengharuskan adanya perbaikan berkelanjutan untuk melatihkan keterampilan berpikir kritis peserta didik demi mencapai salah satu tujuan pendidikan.Kata kunci: Kearipan Lokal, Keterampilan Berpikir Kritis, Pemetaan, Peserta Didik SMP.